(untitled) (Journal of Nobel Medical College, 2012)
Complex partial seizures are characterized by altered awareness of the self and the environment. Consciousness is retained unless secondary generalization occurs. Apart from the area and automatism patients may also experience odd disturbances of thought, emotion, deza vu, Jamai’s vu. depersonalization, derealization or even vivid hallucination of past experience (experiential phenomena). Here we report an adolescent lady presenting with non-convulsive status epileptics manifesting in the form of mood disorder with grandiose delusions of increased ability and identity as well as erotomania. Radio imaging and EEG revealed an epileptic focus originating from the parieto-temporal region. The case report cautions against an organic epileptic seizure that might be mistaken for dissociative, pseudodmentia, paranoid psychosis or even schizophrenia. DOI: http://dx.doi.org/10.3126/jonmc.v1i1.7290 Journal of Nobel Medical College Vol.1(1) 2011 65-67